Effect of Recurrent Heating on Mechanical Properties of Artificial Teeth: A Review - Asmeati, Asmeati; Nur, Rusdi (INTEK: Jurnal Penelitian, 2018)
Nowadays lots of material is produced to increase there-mineralization of tooth enamel. The eggshells are one ofmaterials that can also increase the re-mineralization of toothenamel. Eggshells are one of calcium carbonate sources with levelsof 95%. The egg produces waste in the form of eggshells. One ofthe alternatives in tackling the eggshells is to turn it into a calciumcompound. It is the main ingredient of bones and enamel tooth.This paper is proposed to investigate the effect of recurrent heatingon mechanical properties of artificial teeth. This review wasdescribed some study experimental that was performed to heat thespecimen with 20oC, 40oC, 100oC, and 120oC. The heating result ofspecimen was observed to determine the hardness using Brinneland Vickers scale. It was concluded that the higher of heatingtemperature will decrease the hardness of denture base acrylic.